Design of NiOx/Carbon Heterostructure Interlayer to Improve Hole Extraction Efficiency of Inverted Perovskite Solar Cells. Issue 19 (13th September 2021) - Yin, Xin; Zhai, Jifeng; Ingabire, Providence Buregeya; Du, Pingfan; Chen, Wei‐Hsiang; Song, Lixin; Xiong, Jie; Ko, Frank
Abstract: An efficient hole transport layer (HTL) with desirable charge separation and hole extraction efficiency is crucial for inverted perovskite solar cells. However, the interfacial trap recombination loss and mismatched band alignment limit the actual performance of device, especially the open‐circuit voltage ( V OC ). To address this issue, a unique NiO x /carbon heterostructure is designed as efficient anode interlayer for optimizing the interfacial charge transport dynamics between HTL and perovskite. Such a buffer interlayer can significantly contribute to the improved hole conductivity and hole extraction efficiency at HTL/perovskite interface. Moreover, the more favorable gradient energy level alignment can be formed to increase the interfacial electric field, inhibit the nonradiative recombination, and minimize the V OC loss. Therefore, the champion device achieves 19.51% efficiency with high V OC of 1.13 V, close to the highest power conversion efficiencies of MAPbI3 device. This work suggests that interface design can be an alternative approach to fabricate efficient inverted NiO‐based devices. Abstract : The ration design of interface materials for inverted perovskite solar cell is demonstrated. This new designed NiO x /carbon heterostructure interlayer can enable more favorable gradient energy level alignment, improve the interfacial charge transfer dynamics, and minimize open‐circuit voltage loss for high‐performance P‐I‐N device.